(untitled) (Scientific journal of the Fergana State University, 2026)
This article investigates the concept of “internal form” in word formation by analyzing the views of classical and modern linguists, including Humboldt, Potebnya, and Zvegintsev. The article highlights how internal form serves as a linguistic and psychological mechanism that connects a word’s meaning with national worldview, cognitive perception, and cultural semantics. Examples from Uzbek, Russian, and European languages illustrate the variability and significance of internal forms in lexical development.